Carbon Nanoparticles-Based Sensor Analysis - Taghizadeh Afshari G.; Ahmadi M.T.; Fathi A. (Amirkabir University of Technology, 2025)
In this article, an electrochemical sensor in the form of a field effect transistor is designed and fabricated. This sensor is based on carbon nanoparticles grown between two metal electrodes. These nanoparticles have been synthesized by the electric arc discharge method in suitable environmental conditions and in different lengths from the decomposition of butane gas. Considering this set as a field effect transistor, its channel is always established and it is responsible for detecting the desired material. To check the correct functioning of the sensor, its sensitivity to different concentrations of saltwater was checked and the resistance diagram of the sensor as its electrical output was obtained in the presence of different concentrations of saltwater for different lengths of the channel. ? 2024, Amirkabir University of Technology. All rights reserved.